Analysis of approaches to sterility testing of COVID-19 prevention vaccines - S. M. Sukhanova; A. S. Tikhonova; Z. E. Berdnikova (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Preventive vaccination against SARS-CoV-2 infection is currently receiving close attention in the Russian Federation. Improving public confidence in immunisation with new vaccines largely depends on a guarantee of the absence of side effects caused by contamination. A high risk of contamination is inherent to biological products, including coronavirus prevention vaccines, due to their properties and the nature of raw materials used. This risk adds to the need for using effective contaminant detection approaches.The aim of the study was to evaluate the possibility to improve sterility testing of preventive vaccines against SARS-CoV-2 infection.This article presents an analysis of the procedures proposed by pharmaceutical developers for sterility testing of ten Russian vaccines approved in the country for COVID-19 prevention. The authors considered specific characteristics of these vaccines, including their physical and chemical properties, the presence of antimicrobial components, and other critical factors affecting the correctness of the experimental setup. The results suggest that it is possible to improve sterility testing. According to the authors, the main directions for its improvement are the proposal to develop an alternative procedure based on compendial method 2 (OFS.1.2.4.0003.15, Ph. Rus. XIV), as well as the use of a universal culture medium. If used for refining the established procedures and developing new ones, the authors’ recommendations will improve the reliability and applicability of sterility testing during both manufacturing and pre-approval regulatory assessment of updated coronavirus vaccines for subsequent release to the market. The proposed approaches can be applied to testing other medicinal products for sterility.